Estudo de estabilidade e compatibilidade do cetoconazol - Lopes, Mariana Silva (2019)
Ketoconazole (CTZ), an antifungal agent responsible for the inhibition of 14-α-demethylase sterol, was approved in 1981 in the United States for use in this type of treatment. The drug-excipient compatibility study is an important step in preformulation studies when developing pharmaceutical formulations. Interactions between drug and excipients may affect the chemical nature, stability, bioavailability and consequently the therapeutic efficacy and safety of the drug. The main purpose of this study was to study the compatibility of ketoconazole with the excipients corn starch, microcrystalline cellulose, colloidal silicon dioxide, magnesium stearate, lactose monohydrate and povidone using Differential Scanning Calorimetry (DSC), Thermogravimetry (TG) and Fourier Transform Infrared Spectroscopy (FT-IR) with heating. Binary mixtures in the proportion 50:50 (w / w) between drug and excipient were used to make the study feasible. The temperature extrapolated from the start of the pure drug fusion event (Tonset) and its melting enthalpy value (ΔHf) were compared to the respective values obtained for each of the binary mixtures. Experimental and simulated TG/DTG curves were compared using the Pearson’s correlation coefficients to evaluate the possibility of incompatibilities through the formation of volatile degradation products. The data obtained from the FT-IR spectra were analyzed using chemometric tools, using the Multivariate Curve Resolution - Alternated Least Squares (MCR-ALS) method, in which the spectra were treated mathematically, thus enabling a corroboration of the results obtained by through DSC and TG/DTG techniques, allowing to verify possible incompatibilities between drug and excipients. Ketoconazole has been shown to be incompatible with the excipients starch, colloidal silicon dioxide and lactose monohydrate.